How do you find the derivative of y=3(x^2+1)(2x^2-1)(2x+3)?
3 Answers
Jun 18, 2018
Explanation:
After the formula
we get
Expanding and combining like terms we obtain
Jun 18, 2018
Explanation:
Here we will be using the product rule:
When the expression is simplified, it becomes:
Hope that makes sense!
Jun 18, 2018
Explanation:
"differentiate each term using the "color(blue)"power rule"
•color(white)(x)d/dx(ax^n)=nax^(n-1)
"expanding the factors gives"
y=12x^5+18x^4+6x^3+9x^2-6x-9
dy/dx=60x^4+72x^3+18x^2+18x-6